2012
DOI: 10.1371/journal.pone.0048581
|View full text |Cite
|
Sign up to set email alerts
|

Male-Specific Differences in Proliferation, Neurogenesis, and Sensitivity to Oxidative Stress in Neural Progenitor Cells Derived from a Rat Model of ALS

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive motor dysfunction and the loss of large motor neurons in the spinal cord and brain stem. A clear genetic link to point mutations in the superoxide dismutase 1 (SOD1) gene has been shown in a small group of familial ALS patients. The exact etiology of ALS is still uncertain, but males have consistently been shown to be at a higher risk for the disease than females. Here we present male-specific effects of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 41 publications
2
15
0
1
Order By: Relevance
“…To date, various studies have assessed neurogenic function in ALS animal models ( Table 1 ), namely in transgenic mice and rats expressing the mutation in the SOD1 gene ( Warita et al, 2001 ; Chi et al, 2006 , 2007 ; Liu and Martin, 2006 ; Murphy, 2009 ; Li et al, 2012 ; Khalil and Lievens, 2017 ). Within this scenario, Li et al (2012) have reported that mSOD1-G93A rats show a significant reduction in fetal tissue derived NSCs proliferation ( Li et al, 2012 ). In agreement, Liu and Martin (2006) have also observed altered proliferative capacity in all neurogenic niches (SVZ, OB, and hippocampal DG) of the mSOD1-G93A transgenic mouse model.…”
Section: Changes In Neurogenic Function In Alsmentioning
confidence: 99%
“…To date, various studies have assessed neurogenic function in ALS animal models ( Table 1 ), namely in transgenic mice and rats expressing the mutation in the SOD1 gene ( Warita et al, 2001 ; Chi et al, 2006 , 2007 ; Liu and Martin, 2006 ; Murphy, 2009 ; Li et al, 2012 ; Khalil and Lievens, 2017 ). Within this scenario, Li et al (2012) have reported that mSOD1-G93A rats show a significant reduction in fetal tissue derived NSCs proliferation ( Li et al, 2012 ). In agreement, Liu and Martin (2006) have also observed altered proliferative capacity in all neurogenic niches (SVZ, OB, and hippocampal DG) of the mSOD1-G93A transgenic mouse model.…”
Section: Changes In Neurogenic Function In Alsmentioning
confidence: 99%
“…In the female mouse brain the X-linked inhibitor of apoptosis protein (XIAP) gene showed greater expression at baseline, and greater reduction upon ischemia than in males, consistent with preferential activation of CASPASE 3, and these differences were independent of the presence of gonads and estrogen supplementation [222]. In addition, the differences in rodent brain stress resistance are observed in neonates, as well as in cultured cells [230234]. Sex-specific differences in susceptibility to apoptosis were apparent in mouse embryonic cells where female cells were more sensitive to apoptosis induced by ethanol and camptothecin [235, 236].…”
Section: Sex-specific Autophagy and Apoptosis In Mammalian Cells And mentioning
confidence: 99%
“…Susceptibility to exogenous oxidative stress was measured as described previously (Li et al, 2012). Briefly, myogenic progenitors were plated down onto poly-L-lysine- and laminin-coated coverslips, and cultured in terminal differentiation medium in 24-well plates.…”
Section: Methodsmentioning
confidence: 99%